Physical performance of the students of music schools - Apanowicz, Mateusz (Journal of Education, Health and Sport, 2018)
Introduction. Broadly understood physical performance constitutes a basis for the techniques of playing musical instruments. All motoric skills are meaningful here as they account for the widely interpreted movement and intellectual efficiency. Material and methods. The study included 393 students from randomly selected music schools in Poland and Germany. The level of physical performance was assessed by means of the Eurofit test in each of the schools. Summary. Among the students of both sexes, the average values obtained in the analysed tests did not reveal many differences. Average results achieved in the agility run revealed a decreasing tendency in grades 1 – 4 and an increasing trend in grades 5 and 6. An exception were boys’ results obtained in the cardiorespiratory test in grades 3, 4 and 6, which considerably differed from the results of other students involved in the study and in the muscle endurance test (functional strength) with the average results of boys tending to increase over subsequent years. It should be also emphasized that in the upper limbs speed test the results obtained by the girls of grade 5 definitely surpassed the level of other students.